Supply Chain Management for Pressure Vessel Fabrication Based on Design Pressure and Capacity Specifications - Darmawan, Didit; Suharyono, Dedik (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2026)
Pressure vessel fabrication requires precise material specifications derived from design pressure and capacity. These specifications guide procurement planning, supplier selection, and inventory management. Material quantity calculation must consider yield factors and nesting efficiency. Supplier selection employs multi criteria weighting with quality as primary requirement due to safety risks. Inventory management faces challenges from large material dimensions, corrosion risks, and high holding costs. Just in time or consignment strategies may suit reliable suppliers. Material traceability systems and complete documentation are mandatory for regulatory certification. Collaboration with suppliers during design phase reduces custom dimension orders. Technology adoption including ERP and blockchain improves supply chain visibility. Performance metrics such as perfect order fulfillment enable continuous improvement.